Beispiele für Zusammenarbeit und Geschäftsbeziehungen Zwischen… Energieunternehmen aus Österreich und Deutschland in den Jahren 2008–2013 - Paszyn, Maciej (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
The aim of this article is to present the collaboration between companies in the energy sector in Austria and Germany. During the financial crisis 2008–2012, Austrian energy companies became important partners of German firms supplying Germany with the energy necessary for industries and households. In addition, companies from Austria and Germany participated in the first phase of construction of the pipeline Nabucco. Thanks to manage capital of Austrian and German companies, they may now jointly pursue the objective of expansion in third countries market. After the energy reform, known as the Energiewende, Germany needs more electricity, which largely provide the company with a smaller, but equally high-tech Republic of Austria.